Implications of specific lysine residues within ataxin-3 for the molecular pathogenesis of Machado-Joseph disease - Pereira Sena, Priscila; Weber, Jonasz Jeremiasz; Bayezit, Sercan; Saup, Rafael; Incebacak Eltemur, Rana Dilara; Li, Xiaoling; Velic, Ana; Jung, Jaqueline; Macek, Boris; Nguyen, Huu Phuc; Riess, Olaf; Schmidt, Thorsten (Frontiers in Molecular Neuroscience, 2023)
Lysine residues are one of the main sites for posttranslational modifications of proteins, and lysine ubiquitination of the Machado-Joseph disease protein ataxin-3 is implicated in its cellular function and polyglutamine expansion-dependent toxicity. Despite previously undertaken efforts, the individual roles of specific lysine residues of the ataxin-3 sequence are not entirely understood and demands further analysis. By retaining single lysine residues of otherwise lysine-free wild-type and polyglutamine-expanded ataxin-3, we assessed the effects of a site-limited modifiability on ataxin-3 protein levels, aggregation propensity, localization, and stability. We confirmed earlier findings that levels of lysine-free ataxin-3 are reduced due to its decreased stability, which led to a diminished load of SDS-insoluble species of its polyglutamine-expanded form. The isolated presence of several single lysine residues within the N-terminus of polyglutamine-expanded ataxin-3 significantly restored its aggregate levels, with highest fold changes induced by the presence of lysine 8 or lysine 85, respectively. Ataxin-3 lacking all lysine residues presented a slightly increased nuclear localization, which was counteracted by the reintroduction of lysine 85, whereas presence of either lysine 8 or lysine 85 led to a significantly higher ataxin-3 stability. Moreover, lysine-free ataxin 3 showed increased toxicity and binding to K48-linked polyubiquitin chains, whereas the reintroduction of lysine 85, located between the ubiquitin-binding sites 1 and 2 of ataxin-3, normalized its binding affinity. Overall, our data highlight the relevance of lysine residues 8 and 85 of ataxin-3 and encourage further analyses, to evaluate the potential of modulating posttranslational modifications of these sites for influencing pathophysiological characteristics of the Machado-Joseph disease protein.